The mediating role of resilience between positive personality traits and hopes of emerging adults: A structural equation modeling analysis - Esra Eren; Funda Ergüleç; Ahmet Kara (Journal of Pedagogical Research)
Understanding how resilience evolves across the lifespan is crucial for the development of targeted interventions and strategies aimed at promoting resilience. This study aims to investigate the complex interplay between resilience, positive personality traits, and hope in emerging adults. The criterion sampling method was employed to select participants falling within the specified age range. The study group consists of 353 university students aged 18-23, including 267 women and 86 men, all classified as emerging adults. Three different data collection tools were used in the study: The Big Five Inventory, The Brief Resilience Scale, and Dispositional Hope Scale. The data were evaluated with two-stage structural equation modelling. According to the results of this study, positive personality traits predict resilience at a moderate level. Simultaneously, resilience predicts hope at a moderate level. Additionally, positive personality traits predict hope at a high level. Finally, resilience plays a significant role in bridging personality traits and hope, serving as a buffer to protect both physical and psychological well-being. Recognizing the pivotal role of resilience, particularly in the context of education, this study emphasizes the importance of emerging adults’ awareness of their personality traits and the encouragement to cultivate and effectively utilize positive personality traits. The study underscores the critical role of resilience in bridging positive personality traits and hope, with implications for educational institutions and the broader community.